Survey Penyebab Rendahnya Keberhasilan Pemberian ASI Pasca Melahirkan di RS M. Sani - Christien Natalia Hutabarat; Jasrida Yunita; Tri Putri (Jurnal Medika: Medika, 2026)
Low rates of successful breastfeeding in the postpartum period remain a public health concern, affecting the nutritional status and health of both mothers and infants, particularly within healthcare facilities. This study aimed to analyze the factors contributing to low postpartum breastfeeding success at RSUD M. Sani Karimun as a basis for developing contextual and applicable interventions. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and document reviews involving postpartum mothers and healthcare workers in the maternal and postnatal wards. Data analysis was conducted using the problem-solving cycle approach, including situation analysis, identification and prioritization of problems using the Urgency, Seriousness, and Growth (USG) method, and root cause analysis using a fishbone diagram. The findings indicate that low postpartum breastfeeding success is influenced by limited numbers and competencies of healthcare workers in breastfeeding counseling, suboptimal implementation of early initiation of breastfeeding and lactation support, limited educational media and supporting facilities, low family support, and environmental influences, including the promotion of formula milk. This study concludes that improving postpartum breastfeeding success requires strengthening breastfeeding-friendly services in hospitals through scheduled breastfeeding education, consistent implementation of standard operating procedures, capacity building of healthcare workers, and sustained family involvement and hospital policies.